Avaliação dos aspectos clínico-nutricionais e da autopercepção corporal e alimentar de adolescentes atendidos no núcleo de investigação em anorexia e bulimia do hospital das clínicas - Universidade Federal de Minas Gerais - Mariana Ribeiro de Almeida Lana (2011)
Eating Disorders, especially Anorexia Nervosa and Bulimia Nervosa, are presented in scientific literature as psychiatric diseases of multifactorial etiology, affecting mainly young females. The clinical nutritional and psychological changes can compromise the quality of life of patients with these diseases. However there are few studies on the clinical and nutritional food and bodily perceptions of patients who come to services specialize in eating disorders. This study aimed at assessing clinical and nutritional aspects as well as self-perception of body image and diet of patients admitted to the Center for Research in Anorexia and Bulimia, Hospital das Clinicas, Universidade Federal de Minas Gerais (NIAB - HC - UFMG). This was a cross-sectional, observational study that also used methodology of qualitative-quantitative triangulation to account for qualitative data. All patients who came to welcome the NIAB in the period between March and August 2010 were invited to participate. Thirty-eight patients underwent clinical and nutritional evaluation, and semi-structured interviews were conducted. The results showed that most patients were adolescents (52.8%), females (94.4%) who did not exercise, did not consume alcohol and did not smoke. Most of them (47.4%) were well-nourished and with ae proper fat distribution (40%). The survey revealed that the motivational issue for attending a specialized service was predominantly due to psychological questions about the uniqueness of the disease. Most of these individuals showed distortions of body image. Thus, we emphasize the importance of clinical and nutritional assessment and recovery of subjective aspects, linked to the body and feeding in patients with ED. The study also draws attention to the need for further research in order to validate the methods for assessing clinical and nutritional status as well as considers of utmost importance the expansion of the scope of EDstudies to take in consideration what patients tell about their condition, , thus promoting further discussion about eating disorders.